Why Have You Been Silent? The Church and the Abortion Ban in South Africa - Camp, S. Talcott (Columbia Journal of Gender and Law, 1994)
Whether they perform the procedure on themselves or have someone else do it for them, South African women who resort to illegal abortion typically use sharp objects, such as knitting needles, or harsh chemicals, such as chlorides (sold as "Clorox" in the United States). Every year, 300,000 of South Africa’s twenty million women undergo illegal abortions. They constitute about one in twenty-three fertile women. Many tens of thousands of the clandestine, unsterile operations result in infection or uncontrollable bleeding for the woman. The lucky ones receive life-saving medical attention, which often includes the removal of their septic abdominal organs. Others live, but suffer permanent medical trauma. The unluckiest ones die-l,500 to 3,000 every year.’ The discriminatory, interrelated forces that lead women to such fearful methods coalesce in South Africa’s abortion ban, which is still in effect after the April 1994 free elections. Despite the staggering proportions of the phenomenon, the church in South Africa has turned a blind eye and a mute tongue. What are the theological implications of that silence? How is the church called to respond to the medical fallout from South Africa’s abortion ban? To follow its own tenets, what must the church do in the face of a law that, though it causes such anguish, was justified by the apartheid government in terms of Christian principles? In this Article, I argue that it is theologically imperative for the church to end its silence on several issues: the abortion ban, the apartheid government’s use of Christianity to justify the ban, the ban’s effect on women’s lives, and the church’s own tacit but powerful role in relegating women’s well-being to the bottom of the heap of theological and political values. In ending its own silence, the church will also cease its enforcement of the silence with which so many South Africans continue to have illegal abortions. Examination of the church and the abortion ban involves medical, political, legal, and theological issues. In Part I of this Article, I discuss the theological imperative for the church to end its stubborn ignorance of women’s reality as shaped by the abortion ban. Part II is a discussion of the multiple, complex forces that constituted apartheid. Part III addresses the medical impact of the illegality of abortion. In Part IV, I explain the law itself, and its operation in a still-divided society. Part V addresses the role of the church to date. The Conclusion applies the doctrinal concerns of Part I to the current political situation in South Africa.